Rehabilitación de las funciones ejecutivas (2008)
ABSTRACT: The rehabilitation of the executive function , after injures in the frontal lobes , has emerged as a formidable challenge, due to an injury in these areas may cause alteration to a group on neuroanatomical and functional complex systems in several ways. This paper reviews the main anatomical and functional components of the frontal lobes and the rehabilitation programs in which are involved the different altered executive components after brain damage; stressing the importance of covering not only , the cognitive facts but also , the emotional and psychosocial ones, as a consequence of trauma. Subsequently, limitations of the program are presented, derived from the difficulty of rehabilitating aspects related with what is known as conscience and the difficulties in delimiting the range of the concept and the lack of consensus with its essential components.